Implementation School Based Local Wisdom in the Learning Process in Elementary Schools - Wahyudi, Agung; Edward, Bash Asbe (Journal of Basic Education Research, 2024)
Purpose of the Study: This research aims to explore the understanding of school leaders, development teams, and teachers regarding the concept of school-based local wisdom. Methodology: This study employs a descriptive qualitative approach. The subjects include the school principal, development team, teachers, and students. Data was collected through observations, interviews, and documentation, with data analyzed using reduction, display, and conclusion-drawing techniques. The validity of the data was ensured using triangulation of techniques and sources. Main Findings: The research findings reveal a shared understanding among the school principal, development team, and teachers regarding integrating local wisdom into school-based education. The principal views school-based local wisdom as incorporating cultural elements into the learning environment. The development team interprets it as applying local cultural practices within the curriculum, while teachers link the learning process to local wisdom in the community. At Sendangsari Elementary School, local wisdom such as traditional foods, karawitan (Javanese music), dance, and batik are actively developed. The school employs five key strategies: forming collaborative teams, preparing supporting facilities, implementing strategic plans, partnering with external parties, and fostering community collaboration. Novelty/Originality of this Study: This research offers new insights into integrating local wisdom into curricular and extracurricular activities at the primary school level. It highlights the types of local wisdom developed and presents a model for schools to collaborate with communities and external stakeholders, contributing to the academic discourse on culturally responsive education.